The phenomenon of yearning in the poetry of Jouhdor pen Moaweya - طه نزيهة (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research work deals with the phenomenon of yearning in the poetry of Jouhdor pen Moaweya which is one of the phenomenon that occupied agreat deal in oyr poetic inheritance the old and the modern, by which the poets expressed their suffering and made it contain right feeling which tells the pain of expariation and its bad pain. Jouhdor pen Moaweya is one of the brave thieves and the poets who were expariated of their homes and stayed along time in the prisons of al-Hajjaj which led to agreat home sickness, which was expressed by his soul to show agreat home sickness which was done by his obliged expariation of his home and family. We want to follow the phenomenon of yearning in his poetry by agood and right reading of his poem "al Noonea" by which many different feelings were mixed depending on the stylistic and expressive phenomena and the style of the artistical forming by which he expressed of this inside feeling of the pain of yearning and home sickness.